Les attentes des enseignants par rapport aux capacités des élèves à agir au comité des élèves à l'école primaire - Catherine Pache-Hébert; France Jutras; Jean-Herman Guay (Nantes Université, 2015)
The student council is integrated in schools to encourage students' participation in school governance and contribute to their education for democratic citizenship. The role of the teacher supervising the student council is complex as he seeks a balance ensuring both the well-functioning of the committee and allowing students to make decisions. Teachers hold diverse understandings of students' capacities to do so and do not necessarily know all the dimensions of their supervision role at the student council. This study aimed to highlight teachers' expectations about students' capacities to take action at the student council. Data were collected through a professional development process offered to 10 elementary teachers supervising the student council of their school. Semi-structured interviews and participant observation were conducted. Content analysis combines qualitative and quantitative methods and includes the following: statement development based on verbatim transcriptions and their quantification, principal component analysis and a validation based on verbatim transcriptions and observation notes. Three profiles were observed among teachers: the confident, the ambivalent, and the reluctant ones. These profiles showed the teachers' diverse expectations about their supervision role, the place given to students in decision making, and the notion of students' ability to exercise their governance. This study highlights the need for teachers supervising student councils to modulate their expectations about students' capacities to take action in the activities of the student council. It also shows that training and coaching is beneficial to the professional development required to supervise the student council.